Controlling Light in Optically Induced Photonic Lattices - Terhalle, Bernd; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Discrete periodic structures play an important role in physics, and have opened up an exciting new area of investigation in recent years. Questions relating to the control of light in such structures still represent a major challenge. It is this highly active field that is adressed in the present thesis. Using the model system of a photorefractive nonlinearity that allows one to simultaneously create and control photonic lattices by light, the author obtains a comprehensive picture of the control of nonlinear and quantum optics phenomena in photonic lattices. He describes and demonstrates experimentally for the first time resonant transitions in two-dimensional hexagonal lattices, including Rabi oscillations and Landau-Zener tunneling, as well as the direct control and exploitation of these transitions. A particular highlight of this thesis is the study of soliton-cluster switching and control of Zener tunneling.
Motivation and Outline -- Light Propagation in Nonlinear Periodic Media -- Optically Induced Photonic Lattices -- Resonant Rabi Oscillations and Interband Transitions -- Nonlinear Light Localization -- Summary and Outlook -- Appendix.
Keywords: Physics; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Nonlinear Dynamics; Quantum Optics; Nanoscale Science and Technology